The social determinants of polymorphous prejudice against lesbian and gay individuals: the case of Portugal - Lopes, D.; Oliveira, J. M.; Nogueira, C.; Grave, R. G. (Sexuality Research and Social Policy, 2017)
In the present article, we analyze polymorphous prejudice against lesbians and gays according to a sample of Portuguese heterosexual individuals. We tested the differential importance of demographic-, ideological-, and psychological-level variables to predicting this phenomenon. Our results show that male, Catholic, right-wing respondents with fewer lesbian and gay (LG) friends prove the group exhibiting the highest levels of polymorphous prejudice. Furthermore, the introduction of psychological-level variables into the regression models increased the explained variance in polymorphous prejudice, above and beyond the remaining predictors. Additionally, we report different patterns of results when deploying regression analyses at the level of the sub-scales of polymorphous prejudice. We discuss our results within the light of contemporary sexual prejudice frameworks before reviewing the utility of results to interventions targeting discriminated LG individuals.